PERANCANGAN MULTIPURPOSE WHEELCHAIR - Nusantara Fathonisyam Putra Ardhi; Batan Made Londen I (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2018)
The limitations of the rooms in the hospital may be reasonable, but it will be a problem if this happens at certain times when there is an over the quota of patients such as during an outbreak of Dengue Fever or in the event of a natural disaster. Generally, patients must be willing to sleep on the floor just because of the limitations of the inpatient room and also the bed. To help overcome this problem, especially to help paramedic needs, a multipurpose wheelchair is designed so that in addition to being able to be used as patient transportation, it can also be used as an examination table. The method used to develop the wheelchair starts from an inventory of wheelchair needs, concept development, and selection. The reference used for concept development is a conventional wheelchair while the criteria set for the variety of concepts are the function, operational ease and convenience (wheelchair wear ergonomics). As the central part of the wheelchair, the frame is made of stainless steel pipes. To keep the seating position stable, the swing arm is used as a place to hang the seat on the mainframe. The cross position in the middle of the frame functions to keep the wheelchair symmetrical and can be folded when not in use. Semicircular discs with seven keyholes, each of which is spaced 150, are used as a system for backrest mechanisms to allow them to lie down. The rack and pinion system is used as a mechanism for wheelchair lifting when it is functioned as an examination table. Ergonomics analysis with the help of Catia software using the RULA method, the grand score obtained is 3. So that the design of the wheelchair is quite safe Keywords: Wheelchairs, multipurpose, stable, foldable, rack and pinion and ergonomic